(3OQGSI ebGQfI s - (3YHGS Ydj(B, (3SdeGfs ((3GdEScfOQjI(B;(3HZOGO(B:s (3OGQ GdJYdje GdLGeYj(B;(3ecJH GdgGTej ddcJGH GdLGeYj(B,s, 2018)
(3JfGhd gPG GdcJGH ehVhY eSDhdjI eQGbH GdMSGHGJ aj ecGaMI GdaSGO aj GdTQcGJ GdeSGgeI, MjK JMOK aj GdaUd GdChd Yf GdGWGQ GdbGfhfj deQcR eQGbH GdMSGHGJ aj GdTQcGJ GdeSGgeI , aj Mjf NUU GdaUd GdKGfj ddaSGO aj GdTQcI GdeSGgeI hZSjd GdCehGd, haj GdaUd GdKGdK GdeSDhdjI GdbGfhfjI deQGbH GdMSGHGJ(B.s
(3edGMb U(B.187 (3HHdjhZQGajG U(B.191s
Keywords: (3GdTQcGJ GdeSGgeI (B- (3eMGSHIs; (3GdaSGO GdEOGQjs